Optimization of Anti-Inflammatory Activity of Rauvolfia tetraphylla L. Crude Extracts Using Response Surface Methodology - Nallasamy, Lavanya; Swaminathan, Amutha; Krishnamoorthy, Deepika; Murugavelu, Girija Sangari; Selvaraj, Swarna Lakshmi (Indian Journal of Pharmaceutical Education and Research, 2024)
Background The background of this study revolves around Rauvolfia tetraphylla and its potential anti-inflammatory properties. To explore the anti-inflammatory activity of crude extracts obtained from the leaf and fruit of R. tetraphylla, with the goal of identifying natural compounds that could serve as safer and more effective alternatives to conventional non-steroidal anti-inflammatory drugs. Objectives Aim of the study is to identify the most potent anti-inflammatory activity from Rauvolfia tetraphylla and optimizing the synthesis using Response Surface Methodology (RSM). The RSM analysis is to determine the influence of selected independent variables on dependent variables of the anti-inflammatory properties of R. tetraphylla, an endangered medicinal shrub. Materials and Methods The anti-inflammatory activity of various crude extracts (hexane, chloroform, ethyl acetate and methanol) derived from the leaf and fruit of R. tetraphylla, was investigated using an in vitro assay based on denaturation of protein and utilize Response Surface Methodology to optimize the anti-inflammatory activity of the extracts using bovine serum albumin as the test protein. Results The results showed that the ethyl acetate extract of fruit exhibited greatest inhibitory effect. Furthermore, the 3D response surface plot, perturbation plot, and contour plot were successfully obtained, indicating the interdependence of the four factors on the anti-inflammatory activity. By optimizing the parameters, it may be possible to enhance the anti-inflammatory activity, thereby maximizing the plant’s therapeutic potential. Conclusion These findings suggest that R. tetraphylla leaf and fruit could serve as a potential source of anti-inflammatory agents with better safety and efficacy profiles compared to Non-Steroidal Anti-inflammatory Drugs.
Keywords: Rauvolfia tetraphylla; Anti-inflammatory; Protein denaturation; RSM; Protein denaturation